Rhizospheric Lactobacillus plantarum (Lactiplantibacillus plantarum) strains exhibit bile salt hydrolysis, hypocholestrolemic and probiotic capabilities in vitro - Neelja Singhal (Nature Portfolio, 2021)
Abstract Lactobacillus plantarum (renamed as Lactiplantibacillus plantarum) has been isolated from many sources but very rarely from rhizospheric soil. This is the first report on isolation and assessment of probiotic capabilities of L. plantarum strains isolated from rhizospheric soil. The isolates were confirmed by 16S rRNA gene sequencing and named as NS14, NS16 and NGG. All the isolates were evaluated for bile salt hydrolysis, hypocholestrolemic potential and probiotic attributes. Our results indicated that all the strains harboured bsh and showed in vitro cholesterol assimilation capabilities which increased when bile salts were also present in the culture medium. Also, all the strains remained viable at high temperatures and in the presence of NaCl, lysozyme, simulated gastric juice, bile salts and, exhibited auto- and co-aggregation capabilities. Additionally, L. plantarum strain NS14 survived in the presence of phenols, acidic environment (pH 2–3) and was resistant to many clinically relevant antibiotics. Since, L. plantarum NS14 exhibited most of the desirable and essential characteristics of a probiotic it should be further investigated as a potent probiotic with an additional benefit as a hypocholesterolemic biotherapeutic. Moreover, rhizosphere can be explored as a useful ecological niche for isolating microorganisms with biotechnological and probiotic potential.